EVALUASI IMPLEMENTASI MANAJEMEN RISIKO PADA PROSES PEMBERIAN KREDIT - RICA DELIANDRA (Jurnal Ekonomi dan Bisnis Airlangga, 2019)
Introduction: This research evaluates the implementation of credit risk management in the Bank “X”, which is to mitigate risks. The focused is on the application of risk management components, namely the identification , measurement, control , and monitoring of credit risk. Methods: This study uses Bank "X" one of the bank “non-devisa” in Surabaya. Data is obtained from interviews and documentation. The analysis was performed by descriptive qualitative method, i.e by comparing the real conditions conducted by the Bank "X" with thetheoretical basis of risk management, Bank Indonesia’s Regulation, Standard Operating Procedures (SOPs), and the policy of the Bank "X".Results: The result reveals that the credit risk management in Bank “X” Surabaya has been implemented although some are not yet optimal.Among the optimal ones are Standard Operating Procedures (SOPs) and policies of the Bank "X" is not implemented by the corresponding sectionin the lending process. Further, it is also found the manager of risk management has a low risk appetite.Conclusion and suggestion: The recomendation for Bank “X” are to continue and to improve the implementation process comprehensively, in accordance with the changing of the business complexity. Standard Operating Procedures (SOPs) still needs improvement i.e. the learning process and practical training to support the risk management, improvement on credit exposure management and the Credit Risk Rating (CRR).